Perceived stress and sleep quality among master's students in social work. Issue 5 (4th July 2022) - Lee, Hyunji; Rauktis, Mary E.; Fusco, Rachel A.
ABSTRACT: Poor sleep quality is prevalent in professional graduate school students due to academic- and work-related stress. In addition, it has been found that high levels of perceived stress, including lifetime traumatic stress, are significantly associated with poor sleep quality. This study surveyed 196 MSW students from a university in the United States. The study revealed that the majority of MSW students had poor sleep quality, which was significantly associated with higher levels of perceived stress, poorer sleep habits and environments, and a greater number of experiences of lifetime traumattagdtic events. Importantly, perceived stress and lifetime experiences of traumatic events became less strongly associated with sleep quality after adding sleep habits and environment as a control variable. Findings from the study can guide social work educators to consider incorporating sleep hygiene education into self-care practice programs and offer MSW students these interventions within the MSW curriculum.